Loyalitas Muzakki: Tinjauan Analisis Bibliometrik - Hariya Toni; Alda Srilupita (Jurnal at-Taghyir: Jurnal Dakwah dan Pengembangan Masyarakat Desa, 2024)
This study aims to examine how the loyalty of muzakki in paying zakat in amil zakat institutions.   Due to the lack of trust of muzakki towards zakat institutions, they prefer to pay zakat directly to 8 asnaf who are entitled to receive zakat. This study involves the bibliometric method, specifically the bibliometric approach, to analyze scientific publications relevant to the loyalty of muzakki in paying zakat. The use of bibliometric methods to provide comprehensive insights into research trends and fill knowledge gaps for future research. The author's analysis stage is carried out by searching for data in Dimensions, the search results are analyzed through Network Visualization, Overlay Visualization, and Density Visualization using the Vosviwer application. The results and discussion show a significant development of publications in the last 10 years, with a peak in the number of publications in 2018. Co-authorship analysis shows the relationship between several researchers, while keyword relationship analysis illustrates the diverse research focus. The existence of relationships between researchers and variations in the focus of this research indicate the importance of cooperation and in-depth understanding in maintaining muzakki loyalty in maintaining the stability of zakat income. The conclusion of this research is the need to maintain the trust of muzakki in paying zakat so that the loyalty between muzakki and the institution is maintained forever. With good trust given, it is able to foster loyalty from muzakki towards the institution they trust in paying zakat and also in distributing zakat. Keywords:  Muzakki Loyalty, Zakat and Bibliometrics